Mathematical and computational modelling in matlab for the study of an ORC solar system - Amaral, Gabriela (2017)
The main objective of this paper was to acquire the necessary thermodynamic knowledge in order to perform a thermodynamic and economic analysis of a solar ORC system of capacity of 10KW. For this, a model and computer program were developed in Matlab R2008a, version 7.6.0, which analyses the efficiency of the collector based on the gross solar radiation introduced and the efficiency of the ORC cycle against the power of the respective radiation. Based on the behaviour of the collector and the ORC cycle, the program returns as outputs the area and quantity of manifold required for the desired power. Through this study it can be concluded that for the best scenario, the collector area required is 1044.1 m2 and collector 590 respectively. The annual profit is 48360€/year and an 8 year payback for the initial investment with the vacuum tube collectors.